Streptococcus thermophilus APC151 Strain Is Suitable for the Manufacture of Naturally GABA-Enriched Bioactive Yogurt - Linares, Daniel M.; O’Callaghan, Tom F.; O’Connor, Paula M.; Ross, R. P.; Stanton, Catherine (Frontiers in Microbiology, 2016)
Consumer interest in health-promoting food products is a major driving force for the increasing global demand of functional (probiotic) dairy foods. Yoghurt is considered the ideal medium for delivery of beneficial functional ingredients. Gamma-amino-butyric acid has potential as a bioactive ingredient in functional foods due to its health-promoting properties as an anti-stress, anti-hypertensive and anti-diabetic agent. Here we report the use of a novel Streptococcus thermophilus strain, isolated from the digestive tract of fish, for production of yoghurt naturally enriched with 2 mg/ml of gamma-amino-butyric acid (250 mg in a standard yoghurt volume of 125 ml), a dose in the same range as that provided by some commercially available gamma-amino-butyric acid supplements. The biotechnological suitability of this strain for industrial production of yoghurt was demonstrated by comparison with the reference yoghurt inoculated with the commercial CH1 starter (Chr. Hansen) widely used in the dairy industry. Both yoghurts showed comparable pH curves [ΔpH/Δt = 0.31-0.33 h−1], viscosity [0.49 Pa.s], water holding capacity [72-73%], and chemical composition [moisture (87-88 %), protein (5.05-5.65 %), fat (0.12-0.15 %), lactose (4.8-5.8 %) and ash (0.74-1.2 %)]. Gamma-amino-butyric acid was not detected in the control yoghurt. In conclusion, the S. thermophilus APC151 strain reported here provides a natural means for fortification of yoghurt with gamma-amino-butyric acid.